Audience research: the case of Zoom national university channel - Suárez Pareja, Fredy Alexander (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
The research seeks to answer the question that asks whether the target presented by the channel Zoom, students and teachers as defined in senior high school and college, is really the audience that watches the channel.To respond to the study of the audience in Medellin, applied to undergraduate students and teachers of the six colleges affiliated to the channel, as in six universities and unaffiliated students and teachers of senior year six schools in the city, with the purpose of inquire the knowledge we have and the consumption made of Zoom.We define a mixed model research, articulating instruments such as surveys, interviews and focus group which allows a more comprehensive analysis of qualitative and quantitative data to establish a broader and deeper perspective of the problem, the results imply that the channel has to make efforts to reach your target audience with greater force.